Raman Spectroscopic Investigation of the Wear Effect on the Titanium Carbonitride/Aluminum Oxide/Titanium Nitride Coated Cutting Tool - Çelik, Sefa; Üllen, Nuray Bekoz; AKYÜZ, SEVİM; Özel, Ayşen E. (Taylor & Francis Inc., 2022)
In this study, micro-Raman spectroscopy technique in combination with multivariate statistical analysis was carried out to investigate the worn surfaces and metallurgical changes in the wear land of chemical vapor deposition-applied titanium carbonitride/aluminum oxide/titanium nitride-coated cutting inserts. To understand the wear process, detailed scanning electron microscopy analysis was also performed. The structural change at the molecular level of the coating due to the wear of the cutting-edge layers was investigated. Tool life was determined at 0.5 mm flank wear of the cutting tool. Thirty-four Raman spectra recorded from the different points of the worn parts of nine cutting inserts were investigated in comparison with the seven spectra of the different points of three unused cutting inserts. The principal component analysis followed by linear discriminant analysis performed on 41 Raman spectral data, clearly separated the samples as worn and unworn cutting inserts, and showed the wear effects. The comparison of the mean Raman spectrum of worn and unworn (unused) cutting inserts showed that the intensities of the aluminum oxide and titanium nitride bands were decreased, whereas the titanium carbide band at 672 cm(-1) was increased, as a result of the wear effect. Moreover, the relative intensity of disordered carbon (D band) band to the graphitic sp(2) bonded carbon (G band) band was found to increase, due to wear.
Keywords: Chemical Vapor Deposition; Crystalline Degree; Multivariate Statistical Analysis; Vibrational Spectroscopy